Renovación y transformación urbana barrio Las Manitas, Ciudad Bolívar (2015)
Located in Ciudad Bolivar, District 19, UPZ 67 Lucero, neighborhood Las Manitas, is taken shape one of the most important projects of mobility in Bogotá; the Air Cable intermodal mobility project. The intervention consists of 4 stations (143 affected allotments) and 24 piles (with 48 affected allotments) generating an impact on the development of public space, that, if not addressed, will be having a negative impact on the situation of these neighborhoods, since most of the town were consolidated under three main aspects: marginalization, informality and segregation. So, we consider relevant to develop a comprehensive approach to an improvement plan for the neighborhood in the bounding area known as the Limas which communicates the Manitas and Manitas 2° area neighborhoods